Attitudes and behaviors shaping household food waste generation: Lessons from Lebanon. (10th October 2018) - Mattar, L.; Abiad, M.G.; Chalak, A.; Diab, M.; Hassan, H.
Abstract: Background: Food consumption and wastage behavior varies across cultures, which warrants investigations in various countries and locations of different income levels. To date, information on the attitudes and behaviors of households in developing countries regarding food waste is scarce. The objective of this study is to assess the household attitudes and behaviors that determine food waste in Lebanon for a better understanding and for tailoring community based interventions. Methods: A questionnaire, composed of 3 sections and 27 questions, was developed to assess the attitudes and behaviors towards food waste in Lebanese households. A convenient sample of 1264 households from the five governorates of Lebanon was interviewed in 2016 and 2017. The variable " eat everything prepared " was used as a proxy for food waste. The effect of various socio-demographic and behavioral factors on household food waste generation across urban and rural areas in Lebanon was estimated by means of a Logistic regression, using STATA. Results: Socio-demographic variables such as employment, education, number of members in the household and income affected food waste volume. Behaviors such as eating out frequently and buying best offers were shown to increase food wastage. Also, beliefs such as feeling guilty decreased food waste generation. Rural households contributed less to food waste generation compared to urban areas. Conclusion: Households contribute significantly to a country's food waste problem through their behavior and beliefs. Our findings showed that various household characteristics and food-related behaviors, attitudes toward recycling and other beliefs affected food waste generation in urban and rural communities of a developing country. Future research is still needed to better understand determinants of food waste at the household level in developing countries. Highlights: Employment, education, no of household members and income affected food waste volume. Practices such as eating out frequently and buying best offers were shown to increase food wastage. Beliefs such as feeling guilty decreased food waste generation. Rural households contribute less to food waste generation.